Examining the relationship between employee benefits and job satisfaction - Yahya, Khulida Kirana; Pangil, Faizuniah; Johari, Johanim; Md Isa, Mohd Faizal; Daud, Zulkiflee (2008)
It is often argued that providing good employee benefits could have a positive impact on employee’s job-related attitudes such as job satisfaction. The purpose of this paper is to report the findings of a study on the relationship between benefits and job satisfaction, conducted on the employees of government agency. The study tested the effects of medical, housing facility, loan facility, educational fund, allowances and paid-leave satisfaction on employees’ job satisfaction. The results of the study showed that only medical, housing facility and paid-leave satisfaction have significant impact on job satisfaction.